Desalination Performance Assessment of Scalable, Multi-Stack Ready Shock Electrodialysis Unit Utilizing Anion-Exchange Membranes - Čížek, Jan (Membranes (Basel), 2020)
Incumbent electromembrane separation processes, including electrodialysis (ED) and electrodeionization (EDI), provide competitive techniques for desalination, selective separation, and unique solutions for ultra-pure water production. However, most of these common electrochemical systems are limited by concentration polarization and the necessity for multistep raw water pre-treatment. Shock electrodialysis (SED) utilizes overlimiting current to produce fresh, deionized water in a single step process by extending ion depleted zones that propagate through a porous medium as a sharp concentration gradient or a shock wave. So far, SED has been demonstrated on small scale laboratory units using cation-exchange membranes. In this work, we present a scalable and multi-stack ready unit with a large, 5000 mm(2) membrane active area designed and constructed at the Technical University of Liberec in cooperation with MemBrain s.r.o. and Mega a.s. companies (Czechia). We report more than 99% salt rejection using anion-exchange membranes, depending on a dimensionless parameter that scales the constant applied current by the limiting current. It is shown that these parameters are most probably associated with pore size and porous media chemistry. Further design changes need to be done to the separator, the porous medium, and other functional elements to improve the functionality and energy efficiency.